Relationship between Pay Management and Organizational Commitment: A Mediating Role of Job Satisfaction - Ismail, Azman; Abdullah, Nik Anis Sazwani Nik; Rauf, Ummu Ajirah Abdul; Yusof, Mohd Yuhafidz Mohd; Ju, Soon-Yew (International Review of Management and Marketing, 2026)
Recent meta-analyses of the global private higher education sector reveal that a well-designed pay system may fail to attract, retain, and motivate employees to achieve its intended objectives if managers do not implement it effectively. This study investigates the interrelationship between pay management and organizational commitment, incorporating job satisfaction as a mediator. A survey-based method was adopted, yielding 325 responses from employees at private universities in Peninsular Malaysia. The SmartPLS software was used to measure the quality of the measurement model and test the structural model. Structural equation modeling tests revealed three important findings: First, pay management can increase job satisfaction and organizational commitment. Second, job satisfaction can increase organizational commitment. Finally, job satisfaction mediates the relationship between pay management and organizational commitment. In terms of theoretical contribution, this study addresses a gap in the current literature by measuring the mediating effect of job satisfaction on the relationship between pay management and organizational commitment. Regarding methodological robustness, the measurement model demonstrated acceptable validity and reliability. In terms of practical contributions, this study helps practitioners understand various perspectives on pay management and plan an innovation-based pay system to improve the performance of private higher learning institutions amid global competition and challenging circumstances.